Indonesia and Malaysia Students’ Quality of Life After the Covid-19 Pandemic: A Mixed Methods Study - Sinaga, Juster Juster; Sarif, Mawaddah; Hassan, Siti Aishah (Jurnal Kajian Bimbingan dan Konseling, 2023)
Learning from home during the COVID-19 pandemic and learning face-to-face at school with strict health protocols during the COVID-19 pandemic have long-term negative effects on the psychological health of students. This situation may impact life quality (QoL). To measure students’ quality of life, mixed methods were adopted. Participants in this research ranged in age from 12 to 19 years. The study involved a total of 139 research participants. Kidscreen-27 questionnaires with a reliability coefficient of 0.913 percent were used. The interviews were conducted according to a set of defined rules. This data was collected online. The analysis was quantitative, qualitative, and descriptive. The majority of Indonesian and Malaysian students’ quality of life fell below the average or “moderate” level (64.7 percent). Malaysian students tend to have a higher higher quality of life than Indonesian students; male students tend to have a higher quality of life than female students; and students aged 12 to 15 tend to have a higher quality of life than students aged 16 to 19 years old. In addition, this analysis found that Indonesian and Malaysian students tend to have a higher “peers and social support dimensions” quality of life. The final finding indicated that students’ quality of life is related to their social interactions, such as school and home activities with friends and family members.